FAKTOR PENGENDALI KELARUTAN SILIKA DALAM LARUTAN TANAH - Linca Anggria; Husnain Husnain; Tsugiyuki Masunaga (Agric, 2020)
Silica is a beneficial element for rice plants which can protect from blast disease, increase stem strength, and alleviate abiotic stress. Silicon in soil solution is affected by several factors such as pH, temperature, organic matter, and redox potential (Eh). This study aims to investigate the controlling factor of Si solubility in soil solution. In the present study, Japanese silica gel (JSG) and Ultisols were collected from Japan. In laboratory experiment, the effects of Ca (calcium), Mg (magnesium) and others on solubility of Si (silica) were investigated. Under submerged condition, ten gram of soil with silica gel, Ca and Mg in plastic tube were incubated at 300C for 29 days. Calcium and Mg were applied into soil, at the concentration of 5, 10, 15 mg Ca L-1(T2, T3, T4 respectively) and 5, 10, 15 mg Mg L-1(T5, T6, T7 respectively). There was two controls as a follow T0 (soil) and T1 (soil + silica gel). During incubation, Si, Ca, Mg, Fe, and Mn concentrations in surface water were measured using ICP spectroscopy at day 8, 15, and 29. The results show the soil before treatment was slightly acidic (pH 5.7) and extractable Si concentration was 267.1 mg SiO2 kg-1. It was classified to be below critical level of available Si for rice (300 mg SiO2 kg-1). Total concentration of Ca and Mg in soil solution were highest for treatment T4 and T7, respectively compared with other treatments. On the first 8 days of incubation, Si released into soil solution was higher in T1 and T2 compared to other treatments. The solubility of Si was significantly positive correlated with Mn, Eh, and negatively correlated with pH, that indicated these were the controlling factors of the Si release in soil solution. There was no correlation between Si and Ca or Mg concentration in soil solution.